Efavirenz Pharmacogenetics and Weight Gain Following Switch to Integrase Inhibitor–Containing Regimens. (17th October 2020) - Leonard, Michael A; Cindi, Zinhle; Bradford, Yuki; Bourgi, Kassem; Koethe, John; Turner, Megan; Norwood, Jamison; Woodward, Beverly; Erdem, Husamettin; Basham, Rebecca; Baker, Paxton; Rebeiro, Peter F; et al.
Abstract: Background: Unwanted weight gain affects some people living with human immunodeficiency virus (HIV) who are prescribed integrase strand transfer inhibitors (INSTIs). Mechanisms and risk factors are incompletely understood. Methods: We utilized 2 cohorts to study pharmacogenetics of weight gain following switch from efavirenz- to INSTI-based regimens. In an observational cohort, we studied weight gain at 48 weeks following switch from efavirenz- to INSTI-based regimens among patients who had been virologically suppressed for at least 2 years at a clinic in the United States. Associations were characterized with CYP2B6 and UGT1A1 genotypes that affect efavirenz and INSTI metabolism, respectively. In a clinical trials cohort, we studied weight gain at 48 weeks among treatment-naive participants who were randomized to receive efavirenz-containing regimens in AIDS Clinical Trials Group studies A5095, A5142, and A5202 and did not receive INSTIs. Results: In the observational cohort (n = 61), CYP2B6 slow metabolizers had greater weight gain after switch ( P  = .01). This was seen following switch to elvitegravir or raltegravir, but not dolutegravir. UGT1A1 genotype was not associated with weight gain. In the clinical trials cohort (n = 462), CYP2B6 slow metabolizers had lesser weight gain at week 48 among participants receiving efavirenz with tenofovir disoproxil fumarate ( P  = .001), but not those receiving efavirenz with abacavir ( P  = .65). Findings were consistent when stratified by race/ethnicity and by sex. Conclusions: Among patients who switched from efavirenz- to INSTI-based therapy, CYP2B6 genotype was associated with weight gain, possibly reflecting withdrawal of the inhibitory effect of higher efavirenz concentrations on weight gain. The difference by concomitant nucleoside analogue is unexplained. Abstract : In an observational cohort, CYP2B6 slow metabolizers had greater weight gain after switch from efavirenz-based to integrase inhibitor (INSTI)–based regimens. In a clinical trials cohort not prescribed INSTIs, slow metabolizers had lesser weight gain with efavirenz plus tenofovir disoproxil fumarate.